학생안전체험관의 적정성 검토의견 분석 - 장용해(Yong Hae Jang); 이영한(Young Han Lee) (KIEAE Journal, 2021)
Purpose: The purpose of this study is to study basic data for quality control of exhibition experience facilities by analyzing the results of the adequacy review of exhibition experience facilities at the safety experience center, measuring the frequency of review matters by construction stage and work field. .Method: This study presents the differentiation of the study through theoretical review and reviews the facility composition and related laws of the safety experience center. Next, after analyzing the case according to the analysis framework, the frequency of review opinions is measured. Result: The conclusion of this study is that first, the review of exhibition experience facilities can be divided into pre-construction stages, construction stages, and construction completion stages for each construction stage. Second, the review opinion showed a high frequency in the order of construction completion stage, construction stage, and pre-construction stage. Third, the frequency of review opinions on construction details, exhibition directing, and experience equipment was high. Fourth, C-1 had a high frequency of space composition and construction details in the pre-construction stage, and construction details and exhibition production were high in the construction stage, and construction details and experience equipment were high in the construction completion stage. C-2 had a high frequency of exhibition production and construction details at the pre-construction stage, and the construction stage had a high frequency of construction details and other items. KCI Citation Count: 0